Cavitation bubble collapse and rebound in water: Influence of phase transitions. (December 2022) - Aganin, Alexander A.; Mustafin, Ildar N.
Abstract: The influence of the mass transfer across the bubble surface due to evaporation and condensation on the cavitation (vapor) bubble collapse and rebound in water under room conditions has been studied. The bubble is spherical with an initial radius of 1 . 92 mm . The dynamics of the vapor in the bubble and the surrounding liquid is governed by the gas dynamics equations. The effects of the liquid viscosity and heat conductivity of both fluids are taken into account. The liquid and vapor states are mainly described by the known wide-range equations by Nigmatulin and Bolotnova. The mass transfer is governed by the accommodation coefficient α a c in the Hertz–Knudsen–Langmuir formula. It has been found that at α a c in the range 0 . 001 − 0 . 075 the vapor in the bubble is homobaric at collapse. As α a c increases in the range α a c > 0 . 075, an isentropic compression wave convergent to the bubble center is formed in the bubble. At focusing of this wave at the bubble center, a divergent (reflected from the center) isentropic compression wave occurs. With rising α a c the intensities of these convergent and divergent waves increase. The divergent wave partially penetrates to the liquid in the form of an isentropic divergent wave. With growing α a c the penetrated wave becomes steeper. At α a c ≈ 0 . 25 the divergent isentropic wave in the bubble transforms into a shock wave during its propagation to the bubble surface. This shock wave partially penetrates to the liquid in the form of a divergent shock wave. At small α a c the outgoing pulse in liquid is shockless. Starting with α a c ≈ 0 . 03, it becomes discontinuous. In the range 0 . 03 ≤ α a c ≤ 0 . 12 the shock pulse results from only large pressure gradients in the liquid in the vicinity of the bubble at the beginning of rebound. In the range 0 . 12 < α a c < 0 . 25 the discontinuous outgoing pulse is formed from the divergent isentropic compression wave arisen in liquid as a result of partial escape of the isentropic wave out of the bubble. At α a c > 0 . 25 the shock pulse is formed directly on the bubbles surface as a result of the partial penetration of the divergent shock wave from the bubble to liquid. The obtained numerical results are in good agreement with available numerical and experimental data. Graphical abstract: Highlights: At α a c ≤ 0 . 075 the vapor compression in the collapsing bubble is homobaric. In 0 . 075 < α a c < 0 . 25 increasingly intensive compression waves arise in the collapsing bubble. At α a c ≥ 0 . 25 a shock wave appears in the collapsing bubble. At α a c ≥ 0 . 03 the outgoing pulse in liquid is a shockwave. The results are in good agreement with available numerical and experimental data.